Reinventing Government In Fraud Prevention In The Public Sector - Nur Illiyyien; Haliah, Haliah; Kusumawati, Andi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Fraud is fraud related to the benefits obtained by someone by presenting something that is not in accordance with the truth. This study aims to provide an overview of how the concept of reinventing government plays a role in fraud prevention in the public sector. The method used by the author in analyzing data is qualitative methods and literature studies as a framework for thinking in writing. Bureaucratic reform has an important role in reducing fraud risk by changing the structure, processes, and work culture within government organizations. This reform helps reduce fraud risk through increased transparency, changes in the supervisory system, use of technology, strengthening internal control, training for government officials, protection for whistleblowers, and application of six of the ten principles of reinventing government, namely: 1) Strengthening communities in local government development, 2) Proactive to minimize the occurrence of more complex and developing problems, 3) Creative and innovative to improve community participation in management and development, 4) Have resilience and do not give up easily, so that productivity in the organization can increase, 5) Realizing a visionary bureaucracy that focuses on institutional goals, and 6) Honest, clean and free KKN with links to human resource reform, law and rule reform, supervisory reform, and accountability reform.